The Compatibility of Sustainability Values and Turnover Intention in Modern Business Organizations - Mardikaningsih, Rahayu; Essa, Nabeela Ebrahem (Metromedia, 2025)
This study examines the alignment of personal-organisational values related to sustainability and its relationship with employee retention through a qualitative literature review. The main focus is the extent to which the alignment of sustainability values between employees and organisations is related to a decrease in turnover intention. The review results indicate that sustainability value alignment is formed through the convergence of individual value orientations with the way organisations formulate, communicate, and implement sustainability in their policies and daily practices. Employees with strong environmental and social values tend to experience positive identification, higher work meaning, and affective commitment when they perceive the organisation to be aligned with these values. In the realm of retention, the literature consistently shows that value-based P–O fit negatively correlates with turnover intention through increased job satisfaction, commitment, and perceptions of organisational support. Conversely, the gap between sustainability claims and actual practices triggers cynicism, decreased trust, and a desire to seek alternative work environments. These findings imply that sustainability management must be integrated with value-oriented HR policies. Theoretically, this study confirms the importance of explicitly incorporating the sustainability dimension into the P–O fit model.